THE IMPACT OF LIVE-STREAMING CONTENT CHARACTERISTICS ON CONSUMERS’ PURCHASE INTENTION FOR AGRICULTURAL PRODUCTS: THE MEDIATING ROLE OF PERCEIVED TRUST - Pan, Yingying; Damit, Dayang Haryani Diana; Guliling, Hasnawati (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Live-streaming for the e-commerce of agricultural products has grown significantly in recent years. Analysing the relationship between its content characteristics and users' purchasing intentions is of great significance for enhancing the competitiveness of live-streaming e-commerce. Current research in this field is still relatively limited. This paper uses questionnaire surveys to gather research sample data. After that, it conducts an empirical investigation of how live-streaming content attributes like visibility, interaction, and enjoyment affect consumers' purchase intentions and how this influence works, all from the standpoint of consumers' perceived trust. The findings of the study indicate that the attributes of high-quality live-streaming content greatly increase consumers' intent to purchase and indirectly affect their purchasing choices by boosting users' perceived trust. In addition, perceived trust serves as an important mediator in the process by which the qualities of live-streaming material impact users' purchase intentions. Based on this, the research suggests that the overall quality of live-streaming content for agricultural products should be emphasised, such as enriching entertainment elements, optimising the visual display of products, and enhancing interactivity, in order to further increase consumers' trust and provide a reference for improving consumers' purchase intention.